Effectiveness of Tax Amnesty Policy in Indonesia: A Comparative Study of Tax Amnesty Policies - Rusdin Nawi (International Journal of Artificial Intelligence Research, 2022)
This research was conducted with the aim of analyzing the differences between Tax Amnesty volume I and volume II, as well as the effectiveness of Tax Amnesty Volume I and volume II to be used as evaluation and consideration in exploring and increasing state revenue from the taxation sector. This research uses a qualitative method with a case study research approach. The data in this research is qualitative data sourced from primary data and secondary data. Data analysis is carried out in several stages, namely data collection, data refinement, data processing, data analysis, and conclusion drawing. The results of this study indicate that the level of compliance of taxpayers who participate in Tax Amnesty is also low, which is still below 5%. Tax Amnesty will attract incoming funds from abroad into the country, the sectors affected by Tax Amnesty are believed to encourage economic growth in Indonesia.